Tyrosine kinome sequencing of pediatric acute lymphoblastic leukemia: a report from the Children's Oncology Group TARGET Project - Loh, Mignon L; Zhang, Jinghui; Harvey, Richard C; Roberts, Kathryn; Payne-Turner, Debbie; Kang, Huining; Wu, Gang; Chen, Xiang; Becksfort, Jared; Edmonson, Michael; Buetow, Kenneth H; Carroll, William L; et al. (Blood, 2013)
One recently identified subtype of pediatric B-precursor acute lymphoblastic leukemia (ALL) has been termed BCR-ABL1-like or Ph-like because of similarity of the gene expression profile to BCR-ABL1 positive ALL suggesting the presence of lesions activating tyrosine kinases, frequent alteration of IKZF1, and poor outcome. Prior studies demonstrated that approximately half of these patients had genomic lesions leading to CRLF2 overexpression, with half of such cases harboring somatic mutations in the Janus kinases JAK1 and JAK2. To determine whether mutations in other tyrosine kinases might also occur in ALL, we sequenced the tyrosine kinome and downstream signaling genes in 45 high-risk pediatric ALL cases with either a Ph-like gene expression profile or other alterations suggestive of activated kinase signaling. Aside from JAK mutations and 1 FLT3 mutation, no somatic mutations were found in any other tyrosine kinases, suggesting that alternative mechanisms are responsible for activated kinase signaling in high-risk ALL.